The native fruits of the United States and their improvement - Harling, Walter (My University, 1894)
Introduction: The awakening of the western races to the importance of fruit in our economy is giving the horticulture a new impetus. So many, varied, and interesting are the lines opening upon its broad domain that it is difficult to choose one of the exclusion of the others. In selecting for consideration the native fruit of the United States I followed an impulse that led one to believe that through them a great advance might be made in fruit production. It will be needless to say to one who glances over these pages that the impulse had a definite basis in fact. In studying out the matter I have sought to add to my previous observation the conclusions of the most eminent horticulturists. First I endeavored to show in what way native are superior to naturalized species. Then in two series I take up the commoner and the less widely known native fruits mentioning under each the varieties to be found, their qualities and peculiarities to some extent, and where I have discovered anything else regarding them that is germain to this subject I have also included that.
Citation: Harling, Walter. The native fruits of the United States and their improvement. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Native; Fruit; Botany; Hybridization; United states; Theses; Manuscripts (documents)